(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
Saving companies as early as possible and providing new opportunities to faltering entrepreneurs has become one of the main priorities of the EU policy. Following the example of American legislation, the EU Commission has recognized the importance of acknowledging the difficulties in doing business and, through the Directive 2019/1023, created a legal basis for harmonized restructuring tools in EU member state. The aim of the Directive is to enable encouragement, reorganization and creation of new opportunities to faltering entrepreneurs. Although the aim of the Directive 2019/1023 is well thought out, its adoption has not been followed by smooth implementation. Many EU Member States used the possibility of extending the implementation deadline and have implemented the Directive 2019/1023, so to speak, at the last minute. One of such countries is the Republic of Croatia, which, with the latest amendments to the Bankruptcy Act from March 2022, passed a series of provisions implementing the goals and solutions from the Directive 2019/1023. This article opens with an analysis of the circumstances that led to the adoption of the Directive 2019/1023 and gives an overview of its objectives and provisions. In addition, the article addresses the short overview of the implementation solutions developed in Austrian and German law, which are role models for Croatian bankruptcy law. The central part of the paper provides a critical analysis of the amended provisions of the Croatian Bankruptcy Act, which implements the Directive 2019/1023 into the Croatian legal system. The authors warn of possible challenges in the enforcement of the objectives of the Directive through the prism of the amended rules of the Bankruptcy Act.